DEVELOPMENT OF AN INTERVENTION TO PROMOTE SELF-CARE: NEEDS ASSESSMENT - Ozola, Aija; Roslova, Zane; Duhovska, Jana; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The global societal challenges reveal decreased ability of people to maintain health and well-being when faced with prolonged stress conditions. Increases in anxiety, depression, and burnout are reported worldwide. The recent research indicates self-care as a useful resource to promote health and well-being and strengthen psychological resilience. The importance and attainability of self-care strategies are the characteristics that may indicate the necessity for self-care behaviour changes by identifying an internal conflict between the two. However, little is known about the determinants of self-care practicing according one’s needs. The study aimed to explore the experts’ perspectives on self-care needs among clinically healthy adults. The risks caused by inadequate self-care practices and the determinants of self-care behaviour change were identified. The interviews with 12 experts in arts therapies and/or health psychology were conducted. The qualitative content analysis was used to process the data. Psychological, health-related, and social risks were the categories of risks identified. The determinants of self-care behaviour change were categorized as knowledge, self-efficacy, attitude, perceived cues to action, planning, awareness, social support, and motivation. The identified items will contribute to evidence-based development of the intervention to promote self-care.